2011
DOI: 10.1590/s1806-66902011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Fungos micorrízicos arbusculares nativos e doses de fósforo no desenvolvimento do amendoim RUNNER IAC 886

Abstract: Resumo -Objetivou-se avaliar a interação entre fungos micorrízicos arbusculares nativos (FMA) com plantas de amendoim (Arachis hypogea) cultivar RUNNER IAC 886, em diferentes doses de fósforo (P). O experimento foi conduzido em casa de vegetação em delineamento inteiramente casualizado, em esquema fatorial (2 x 5), sendo com e sem a inoculação dos endófitos e cinco doses de P (0; 20; 40; 60 e 180 mg kg -1 na forma de KH 2 PO 4 ), com quatro repetições. Avaliaram-se massa seca de: raiz, parte aérea, total, taxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
2
1
2
Order By: Relevance
“…Corroborating with the results of Silva et al (2009), it was observed that the nutrient application (via seeds or leaf) did not affect the peanut seed yield. This result is in contrast with Hippler et al (2011), who reported that nutrient application affects the productivity of peanuts (Arachis hypogea L.). Silva et al (2012), studied the efficiency of micronutrient products on the peanut yield and concluded that there was a significant response of productivity to Mo application, when applied through seeds.…”
Section: Development Of Seedlingscontrasting
confidence: 97%
“…Corroborating with the results of Silva et al (2009), it was observed that the nutrient application (via seeds or leaf) did not affect the peanut seed yield. This result is in contrast with Hippler et al (2011), who reported that nutrient application affects the productivity of peanuts (Arachis hypogea L.). Silva et al (2012), studied the efficiency of micronutrient products on the peanut yield and concluded that there was a significant response of productivity to Mo application, when applied through seeds.…”
Section: Development Of Seedlingscontrasting
confidence: 97%
“…Assessing the interaction between increasing doses of P and native mycorrhizal fungi, Hippler et al (2011) concluded that phosphorus fertilization enhanced the development of peanut plants (Runner IAC 886), regardless the inoculation with native fungi. For Malavolta et al (1997) the P function is related to energy production in plants, stored as adenosine triphosphate (ATP) and adenosine diphosphate (ADP).…”
Section: Resultsmentioning
confidence: 99%
“…Calcium and phosphorus are essential for flowering and the development of pods and seeds, while K promotes the vegetative development DAVIS 1995). However, the responses of peanut crop to fertilization with nitrogen, phosphorus, and potassium are contradictory, with reports of positive (THIMMEGOWDA 1993;MARUBAYASHI et al, 1997;BASU et al, 2008;HIPPLER et al, 2011), negative (GERIN et al, 1996SPINOLA;CÍCERO 2002) and absence of responses (KASAI et al, 1998;PARKER 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Plantas inoculadas com G. rosea apresentaram os maiores índices de dependência micorrízica, entre 40 e 37% nas menores concentrações de P (0 e 75 mg kg -1 de P, respectivamente), dentre todos os tratamentos, enquanto as plantas inoculadas com G. clarum apresentaram dependência micorrízica de 27% na dose 0 mg kg -1 de P (Figura 6). Essa dependência ocorre também em relação a inoculação do amendoinzeiro com FMA nativos em diferentes doses de P, neste caso, plantas inoculadas com G. rosea, sendo que apresentam a maior dependên-cia micorrízica quando supridas com 60 mg kg -1 de P (Hippler et al, 2011). Nas maiores doses de P (150 e 250 mg kg -1 de P) o amendoinzeiro não apresentou dependência positiva para nenhum dos endófitos inoculados.…”
Section: Glomus Clarumunclassified